Institutional Challenges to Romania'a Regional Policy in the Perspective of Accession to the European Union - Daniela-Luminita Constantin (European Regional Science Association (ERSA), 2006)
Starting with 1998, when the process of Romania's accession to the EU was officially launched, the legal and institutional framework for regional development policy has been created, followed by the elaboration of the National Development Plan. As the programming document that builds up Romania's access to the structural-type funds in the pre-accession period and to the structural and cohesion ones after accession to the EU, the NDP responds to both 'internal necessities' and 'external requirements', revealing the philosophy of the EU support via pre-accession instruments, which has a twofold significance: on the one hand the financial aid is viewed as a way of reducing economic and social disparities between the candidate and the EU member countries; on the other hand, working with pre-accession instruments, creating the institutional framework for measures implementation, action monitoring and impact evaluation allow the candidate countries' authorities to get used to European Commission's procedures and, thus, to be prepared for the administration of the much higher amounted financial funds after accession to the EU. Though, in the case of Romania the institutional framework for regional development policy has suffered a lot of changes since 1998, with negative consequences on the absorption capacity of EU funds, serving as a good example for explaining why so many times Romania has been severely criticised by EU for institutional instability and delays in institutional reform. This paper proposes an analysis of Romania's regional development policy in the perspective of accession to the European Union, with a particular emphasis on the institutional transformations and future challenges, especially those referring to the post-accession period. The author's contribution to a recent study on Romania's capacity to absorb the EU funds (developed under the auspices of the European Institute of Romania) will be presented, offering an evaluation of the components that characterise the administrative capacity of absorption in programming field.
Keywords: 330